Physics, asked by yrshelke25, 1 year ago

Please answer this ​

Attachments:

Answers

Answered by nirman95
3

Answer:

Given:

v1 and v2 are the velocities at x1 and x2 from mean position.

To find:

Angular frequency of the particle

Calculation:

For 1st case :

v1 =  \omega \sqrt{ { a}^{2} -  {(x1)}^{2}  }

 =  >  {(v1)}^{2}  =  { (\omega  a)}^{2}  -  {( \omega  \times   x1)}^{2}

 =  >  {( \omega a)}^{2}  =  {(v1)}^{2}  +  {( \omega \times x1)}^{2}

For 2nd case

v2 =  \omega \sqrt{ { a}^{2} -  {(x2)}^{2}  }

 =  >  {( \omega a)}^{2}  =  {(v2)}^{2}  +  {( \omega \times x2)}^{2}

Comparing (ωa)² :

 =  >  {(v2)}^{2}  +  {( \omega \times x2)}^{2}  =  {(v1)}^{2}  +  {( \omega \times x1)}^{2}

 =  >  { \omega}^{2} ( {x2}^{2}  -  {x1}^{2} ) =  {(v1)}^{2}  -  {(v2)}^{2}

 =  >  { \omega}^{2}  =  \dfrac{ {(v1)}^{2}  -   {(v2)}^{2}  }{ {(x2)}^{2} -  {(x1)}^{2}  }

Taking minus sign common :

 =  >  { \omega}^{2}  =  \dfrac{ {(v2)}^{2}  -   {(v1)}^{2}  }{ {(x1)}^{2} -  {(x2)}^{2}  }

 =  >  { \omega}  =  \sqrt \dfrac{ {(v2)}^{2}  -   {(v1)}^{2}  }{ {(x1)}^{2} -  {(x2)}^{2}  }

So final answer is :

  \boxed{ \red{  { \omega} =  \sqrt \dfrac{ {(v2)}^{2}  -   {(v1)}^{2}  }{ {(x1)}^{2} -  {(x2)}^{2}  } }}

Similar questions